2015
DOI: 10.1007/978-3-319-14983-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Water Through Green Roofs

Abstract: How green roofs process water is a critical component of their function and effective management. As green roof technology has spread from northern Europe's relatively cool and humid climate, green roof designs have had to adapt to regional variations in the timing and availability of water. The development of regionally appropriate designs requires a mechanistic understanding of green roof water relations, plant eco-physiology and irrigation technology. Emerging designs effectively match environmental conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 92 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Recently, Van Mechelen et al () also reported spontaneous bryophyte establishment in unirrigated extensive green roofs (up to 60% cover) located in Mediterranean and temperate maritime climates. Owing to their high dispersal capacities, the ability to colonize substrates that are not yet suitable for other species, and high‐water retention capacity, bryophytes have been suggested for use in greening systems (Lambrinos ; Van Mechelen et al ). Additionally, these poikilohydric organisms are capable of surviving long dry periods in a desiccated state without suffering damage and can facilitate the establishment and survival of vascular plants by buffering environmental extremes (Heim et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Van Mechelen et al () also reported spontaneous bryophyte establishment in unirrigated extensive green roofs (up to 60% cover) located in Mediterranean and temperate maritime climates. Owing to their high dispersal capacities, the ability to colonize substrates that are not yet suitable for other species, and high‐water retention capacity, bryophytes have been suggested for use in greening systems (Lambrinos ; Van Mechelen et al ). Additionally, these poikilohydric organisms are capable of surviving long dry periods in a desiccated state without suffering damage and can facilitate the establishment and survival of vascular plants by buffering environmental extremes (Heim et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The proposed terminology will, apart from scientific advantages, help streamline regulations across cities and countries and the design-construction process, and meet the different expectations of stakeholders (Calleja-Perucho, Mazarrón, Pou-Merina, & Cañas-Guerrero, 2015; Mesimäki et al, 2015). Ultimately, policies can be improved across regions (or be region specific, see Lambrinos, 2015), especially in the setting of targets in the face of climate change and increasingly-densified cities.…”
Section: Clarifying Vegetated Roof Terminology -Let's Call a Spade A ...mentioning
confidence: 99%